Nocturnal Blood Pressure Dipping in Acute Ischemic Stroke - Sargento-Freitas, J (2015)
OBJECTIVES: We aim to assess the impact of early nocturnal blood pressure (BP) variation in the functional outcome of patients after an acute ischemic stroke. MATERIALS AND METHODS: We included consecutive stroke patients treated with intravenous thrombolysis (IVrtPA) in a tertiary stroke center. BP measurements were performed at regular intervals throughout day and night during the first 48 h after stroke onset, and subjects were divided into four dipping categories (extreme dippers, dippers, non-dippers, and reverse dippers). Recanalization was assessed by transcranial color-coded Doppler and/or angiographic CT. Hemorrhagic transformation was evaluated at 24 h follow-up CT scan. Functional outcome was evaluated at 3 months after stroke using the modified Rankin Scale. RESULTS: A total of 304 patients were included, mean age 72.80 ± 11.10 years. After 24 h of systolic BP monitoring, 30.59% were classified as reverse dippers, 39.14% as non-dippers, 19.10% as dippers, and 11.18% as extreme dippers. Multivariate analysis did not show an independent association of any dipping class with 3-month functional outcome. Hemorrhagic transformation was not uniform between dipping classes: 25.81% for reverse dippers, 14.29% for non-dippers, 15.52% for dippers, and 5.88% for extreme dippers, P = 0.033. CONCLUSIONS: Nocturnal BP dipping pattern is not associated with functional outcome at 3 months in acute stroke patients treated with IVrtPA. Hemorrhagic transformation was more frequent in reverse dippers.